The Determinants of Environmental Innovations and Patenting: Germany Reconsidered - Tilmann Rave; Frank Goetzke; Mario Larch (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2011)
This paper provides new evidence on the objectives and determinants of different typesof innovations and patents, environmental as opposed to other innovations and patents,and different variants of environmental innovations and patents. We investigate howfirm-specific and sector-specific driving forces differ by innovation type. Moreover, weoutline the functions that different innovation types have for environmental and innovationpolicies. We find that eco-innovators put relatively more attention to cost reduction, inparticular the reduction of energy and resource costs, compared to other innovators.Cost pressure and reliable, predictable and strict framework conditions of environmentalpolicy turns out to be an important driver for more incremental, firm-level eco-innovationscontributing to the diffusion of principally known technologies among firms. By contrast,more far-reaching patented eco-innovations are driven by the opportunity to create newmarkets and by government subsidies.
Keywords: Q55; O33; O38; C25; 330; Environmental innovation; patent; discrete choice models; Umwelttechnik; Patent; Innovation; Unternehmen; Diskrete Entscheidung; Kostenmanagement; Deutschland